ELECTRONIC CONSUMER STYLE INVENTORY: FACTOR EXPLORATION AND MULTI-COMPARISON ANALYSIS - Manoj Kumar Dash,; Anil Kumar, (Asian Academy of Management Journal, 2014)
The objective of this research article is to identify the factors of consumer decision-making style in the context of electronic purchasing and test the significance of these factors on the basis of gender and age of respondents through multi-comparison analysis. Data for this report came from a survey of consumers (N = 411) with a structured questionnaire design. Exploratory Factor Analysis (EFA), ANOVA and Post-hoc (for multiple comparisons) were used to achieve the objectives of the study. To contribute to an internationally valid and reliable research instrument for consumer decision-making style in the context of electronic purchasing, new constructs were identified, which we will call Electronic Consumer Style Inventory (ECSI). Consistent with the hypotheses, in general, the extracted factors in consumers’ electronic buying decision-making style are found to be significant on the basis of respondent gender and age. Customers’ evaluations of e-service quality are critical to service firms that aim to improve their marketing strategies; consequently, accurate measurement of e-service quality is a major concern for management. The resultant implications of this research are discussed by the authors and can help e-vendors and marketing managers achieve a sustainable competitive advantage in global markets and enhance their performance.